1998
DOI: 10.1046/j.1460-9568.1998.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal α6 subunit forms functional heteromeric acetylcholine receptors in human transfected cells

Abstract: We examine some of the biological and physiological properties of the avian alpha6 neuronal nicotinic acetylcholine receptor (nAChR) subunit. We show here that, beginning at embryonic day 5, alpha6 mRNA is abundantly expressed in the developing chick neuroretina, where it coexists with other nicotinic receptor subunit mRNAs such as alpha3, beta2 and beta4. In contrast, alpha6 mRNA is absent from the optic tectum and from the peripheral ganglia. Despite numerous efforts, the alpha6 subunit has long failed the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 32 publications
4
52
0
Order By: Relevance
“…Moreover, and although these studies were done using oocytes manipulated to express disproportionate ratios of subunits, incorporation of nAChR h␤3 subunits present in presumed excess have a dominant-negative effect on the function of all-human ␣2␤2*-, ␣2␤4*-, ␣3␤2*-, ␣3␤4*-, ␣4␤2*-, or ␣4␤4*-nAChR that is reversed upon substitution of mutant, h␤3 V9ЈS for wild-type ␤3 subunits (12). Similar effects are mentioned (but not described in detail) of effects of wild-type or mutant ␤3 subunits on function of ␣6␤2*-and ␣6␤4*-nAChR (11). Interestingly, other studies using chimeric (␣6/␣3) subunits (containing the N-terminal domain of the nAChR ␣6 subunit substituting for that of the otherwise ␣3 subunit) instead of wild-type ␣6 subunits showed potentiating effects of wild-type ␤3 subunit coexpression on ␣6*-nAChR (8).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, and although these studies were done using oocytes manipulated to express disproportionate ratios of subunits, incorporation of nAChR h␤3 subunits present in presumed excess have a dominant-negative effect on the function of all-human ␣2␤2*-, ␣2␤4*-, ␣3␤2*-, ␣3␤4*-, ␣4␤2*-, or ␣4␤4*-nAChR that is reversed upon substitution of mutant, h␤3 V9ЈS for wild-type ␤3 subunits (12). Similar effects are mentioned (but not described in detail) of effects of wild-type or mutant ␤3 subunits on function of ␣6␤2*-and ␣6␤4*-nAChR (11). Interestingly, other studies using chimeric (␣6/␣3) subunits (containing the N-terminal domain of the nAChR ␣6 subunit substituting for that of the otherwise ␣3 subunit) instead of wild-type ␣6 subunits showed potentiating effects of wild-type ␤3 subunit coexpression on ␣6*-nAChR (8).…”
Section: Discussionsupporting
confidence: 57%
“…Chick or rat nAChR ␣6 subunits form functional channels when coexpressed with h␤4 subunits in Xenopus oocytes, but the ␣6 plus ␤2 subunit combination fails to form functional channels (10). Chick ␣6 subunits also formed functional receptors when coexpressed with chick ␤2 or ␤4 subunits in BOSC 23 cells (11). More recently, Kuryatov et al (8) reported functional expression of human ␣6␤4-nAChR in Xenopus oocytes and formation of ligand-binding (nonfunctional) aggregates of ␣6␤2-nAChR.…”
mentioning
confidence: 99%
“…Transient transfections were carried out in the cell line Bosc 23 as described (28)(29)(30). Subunit cDNAs were added to 35-mm dishes in equivalent amounts (2 g of L248T␣7 subunit cDNA and 1 g each of all other subunits) as described (28)(29)(30). More than the 50% of the cells died after transfection with L248T␣7 subunit cDNA, and the survival increased to Ϸ90% when the cells were incubated with the nicotinic antagonist methyllycaconitine (MLA, 2 M).…”
Section: Electrophysiology In Oocytesmentioning
confidence: 99%
“…Whole-cell patch-clamp recordings of AcCho-or nicotine-induced currents (I AcCho and I nic , respectively) were performed on cells continuously superfused with control or agonist solutions via independent tubes positioned 50-100 m from the patched cell and connected to a fast exchanger system. Recordings were performed as described (28)(29)(30). Unless otherwise indicated, cells were voltageclamped at Ϫ50 mV.…”
Section: Electrophysiology In Bosc 23mentioning
confidence: 99%
See 1 more Smart Citation